Analisis Tingkat Keterampilan Passing Bawah Pemain Bola Voli Smp Negeri 1 Bengkulu Selatan - Falenzo, Jerry Cahaya (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the lower passing skills of SMP Negari 11 South Bengkulu volleyball players. This type of research is descriptive quantitative using survey methods and data collection techniques using tests and measurements. The results of this study based on the volleyball game lower passing skills test found that the category was very poor at 0% (0 players), the category was poor at 0% (0 players), the moderate category was 60% (9 players), the good category was 20% (3 players), and the excellent category was 20% (3 people). Based on the results above, it can be concluded that the lower passing skills of SMPN 11 Bengkulu Selatan volleyball players are in the moderate category, namely 15 students or with a percentage of 60%.